The Dynamic Link of Energy Consumption, Economic Growth and Poverty in Eastern Indonesia: Panel VECM and FMOLS Approach - Leiwakabessy, Erly; Payapo, Rukmuin Wilda (International Journal of Energy Economics and Policy, 2022)
This study aims to investigate the pattern of dynamic relationships between energy consumption, economic growth, and poverty in panel data set of 12 provinces of Eastern Indonesia during the period 2009-2019. PVECM and FM-OLS were applied to analyze the dynamic link of the variables both in the short and long term. All secondary data used were collected from BPS and the Ministry of Energy and Mineral Resources. The results of this empirical study in the short term corroborate the neutrality hypothesis, which reveals that there is no short-term relationship in the case of energy-growth nexus, energy-poverty nexus, and poverty-growth nexus. In the long term, empirical evidence corroborates the feedback hypothesis in the case of the energy-growth nexus and poverty-growth nexus. Concerning the long-run energy-growth nexus, the increase in energy consumption has a positive effect on the acceleration of economic growth, and also the increase in economic growth requires the fulfillment of adequate energy consumption. Furthermore, a feedback relationship is found in the poverty-growth nexus case which explains that the progress of poverty reduction is significantly determined by sustainable economic growth that supports several previous studies and the trickle-down economics argument or pro-growth-poverty. On the other hand, widespread poverty has a negative impact on the achievement of economic growth.